Variation in School District Nutrition Policies and Practices: Community Context Matters. Issue 5 (2nd September 2020) - Emley, Elizabeth; Dial, Lauren; Koerten, Hannah; Musher-Eizenman, Dara
ABSTRACT: Background: The school nutrition environment has a large impact on child diet. However, there is a paucity of nationally representative research on factors that predict effective nutrition policies, practices, and education in schools. Purpose: The current study utilized Centers for Disease Control and Prevention (CDC) data from the 2016 School Health Policies and Practices Survey (SHPPS) to explore the impact of poverty and community type (i.e., urban/rural spectrum) on these variables. Methods: Data from the 2016 SHPPS included 740 U.S. public schools. Composite scores were created from survey items related to dietary policies and practices. Results: Schools of greater rurality and urbanicity had more nutrition policies and education but fewer practices than suburban districts. Rural districts generally had fewer nutrition policies, practices, and education than urban districts. Poverty did not consistently predict these variables. Discussion: Community type is a crucial variable in the school nutrition environment and may better explain discrepancies among schools than poverty. Future efforts might focus on improving school nutrition policy and practice adherence, especially in rural areas. Translation to Health Eduation Practice: Further research using nationally representative data can help health educators better understand what interventions may produce the best results within their unique community type.